Relative Bioavailabilities of Lisdexamfetamine Dimesylate and D-Amphetamine in Healthy Adults in an Open-Label, Randomized, Crossover Study After Mixing Lisdexamfetamine Dimesylate With Food or Drink. Issue 6 (December 2016) - Ermer, James; Corcoran, Mary; Lasseter, Kenneth; Martin, Patrick T.
Abstract : Background: This open-label, crossover study examined lisdexamfetamine dimesylate (LDX) and D-amphetamine pharmacokinetics in healthy adults after administration of an intact LDX capsule or after the capsule was emptied into orange juice or yogurt and the contents consumed. Methods: Healthy adult volunteers (N = 30) were administered a 70-mg LDX capsule or the contents of a 70-mg capsule mixed with yogurt or orange juice using a 3-way crossover design. Blood samples were collected serially for up to 96 hours after dose. Pharmacokinetic endpoints included maximum plasma concentration (Cmax ) and area under the plasma concentration versus time curve from zero to infinity (AUC0–∞ ) or to last assessment (AUClast ). Relative LDX and D-amphetamine bioavailabilities from the contents of a 70-mg LDX capsule mixed with orange juice or yogurt were compared with those from the intact LDX capsule using bioequivalence-testing procedures. Results: Geometric least squares mean ratios (90% confidence intervals [CIs]) for D-amphetamine (active moiety) were within the prespecified bioequivalence range (0.80–1.25) when the contents of a 70-mg LDX capsule were mixed with orange juice [Cmax : 0.971 (0.945, 0.998); AUC0–∞ : 0.986 (0.955, 1.019); AUClast : 0.970 (0.937, 1.004)] or yogurt [Cmax : 0.970 (0.944, 0.997); AUC0–∞ : 0.945 (0.915, 0.976); AUClast : 0.944 (0.912, 0.977)]. Geometric least squares mean ratios (90% CIs) for LDX (inactive prodrug) were below the accepted range when the contents of a 70-mg LDX capsule were mixed with orange juice [Cmax : 0.641 (0.582, 0.707); AUC0–∞ : 0.716 (0.647, 0.792); AUClast : 0.708 (0.655, 0.766)]; the lower 90% CI for Cmax [0.828 (0.752, 0.912)] was below the accepted range when the contents of a 70-mg LDX capsule were mixed with yogurt. Conclusions: Relative bioavailability of D-amphetamine (the active moiety) did not differ across administrations, which suggests that emptying an LDX capsule into orange juice or yogurt and consuming it is an alternative to intact capsules. Abstract : Supplemental Digital Content is Available in the Text.